Effectiveness, safety and pharmacokinetics of Polo-like kinase 1 inhibitors in tumor therapy: A systematic review and meta-analysis - Wei, Xiao; Song, Mingzhu; Huang, Chan; Yu, Qiao; Jiang, Guirong; Jin, Guanghao; Jia, Xibiao; Shi, Zheng (Frontiers in Oncology, 2023)
Objective: To provide a systematic review of existing meta-analysis on the efficacy, safety and pharmacokinetics of the novel polo-like kinase-1 (Plk1) inhibitors in various tumor treatments, and assess the methodological quality and the strength of evidence of the included meta-analysis. Methods: The Medline, PubMed, Embase, etc. were searched and updated on 30 June 2022. 22 eligible clinical trials involving a total of 1256 patients were included for analyses. Randomised controlled trials (RCTs) compared the efficacy or safety, or both of any Plk1 inhibitors with placebo (active or inert) in participants. 22 eligible clinical trials involving a total of 1256 patients were included for analyses. To be included, studies had to be RCTs, quasi-RCTs, and nonrandomized comparative studies. Results: A meta-analysis of two trials reported PFS of the overall population (ES, 1.01; 95% CIs, 0.73-1.30, I2= 0.0%, P<0.001) and OS of the overall population (ES, 0.91; 95% CIs, 0.31-1.50, I2= 77.6%, P=0.003). The results of meta-analysis showed that the incidence of AEs in the nervous system was the highest (ES, 0.202; 95% CIs, 0.161-0.244), followed by blood system (ES, 0.190; 95% CIs, 0.178-0.201) and digestive system (ES, 0.181; 95% CIs, 0.150-0.213). Rigosertib (ON 01910.Na) was associated with a decreased risk of AEs in digestive system (ES, 0.103; 95% CIs, 0.059-0.147), but BI 2536 and Volasertib (BI 6727) increased risk of AEs in blood system (ES, 0.399; 95% CIs, 0.294-0.504). Five eligible studies reported the pharmacokinetic parameters of the low dosage (100 mg) cohort and the high dosage (200 mg) cohort, and there was no statistical difference in the total plasma clearance, terminal half-life and apparent volume of distribution at steady state. Conclusions: Plk1 inhibitors do better in improving OS, and they fail to prolong the PFS. The intervention of Plk1 inhibitors was associated with an increased risk of AEs in the hematopoietic circulatory system, with Volasertib (BI 6727) in particular having the highest risk rate and Rigosertib (ON 01910.Na) causing the lowest risk rate. Cancer patients may preferentially receive a low-dose 100 mg Plk1 inhibitor because the pharmacokinetic effects of the high-dose Plk1 inhibitor at 200 mg were not significantly different.